Simple liver cyst. Laparoscopic treatment - Morelli Brum, Raúl; Praderi Gambardella, Luis A; Veirano, Gustavo; Bermúdez, Jorge (Cirugía del Uruguay, 1998)
The authors present a female patient with symptomatic simple cyst of the liver, confirmed by ultrasonography and CAT-scan. There was no personal or family history of ahydatid disease and laboratory tests far this disease were a/so negative. Evacuation and partía/ resection was carried out by means of laparoscopy. The advantages of this access are pointed out, as hospital stay is shortened, postoperative pain decreases, there is a quicker return to work and better cosmetic results.